2016
DOI: 10.1002/hep.28690
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1‐mediated transcriptional regulation of SOX2 is important for self‐renewal of liver cancer stem cells

Abstract: Hepatocellular carcinoma (HCC) is a highly aggressive liver tumor containing cancer stem cells (CSCs), which participate in tumor invasion, therapeutic resistance, and tumor relapse leading to poor outcome and limited therapeutic options. Histone deacetylatase sirtuin 1 (SIRT1) has been shown to be up-regulated in human cancers; however, its role in liver CSCs is unknown. In this study, we explored the biological functions of SIRT1 in liver CSCs. Our data show that SIRT1 is highly expressed in liver CSCs and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 45 publications
6
95
0
Order By: Relevance
“…These observations are further corroborated by patient‐based studies that Sox2 is the most increased gene among core pluripotency factors in premalignant cirrhotic liver, where hepatocytes have already become resistant to TGFβ‐induced mitoinhibition/apoptosis . In addition to being considered as a predictor for poor survival of HCC patients, Sox2 has also been shown to play an essential role in self‐renewal and maintenance of cancer stem‐like cell populations in HCC . Therefore, TGF‐β signaling may counterbalance Sox2 in cancer initiating and progenitor cell differentiation.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These observations are further corroborated by patient‐based studies that Sox2 is the most increased gene among core pluripotency factors in premalignant cirrhotic liver, where hepatocytes have already become resistant to TGFβ‐induced mitoinhibition/apoptosis . In addition to being considered as a predictor for poor survival of HCC patients, Sox2 has also been shown to play an essential role in self‐renewal and maintenance of cancer stem‐like cell populations in HCC . Therefore, TGF‐β signaling may counterbalance Sox2 in cancer initiating and progenitor cell differentiation.…”
Section: Discussionmentioning
confidence: 62%
“…(40) In addition to being considered as a predictor for poor survival of HCC patients, (41) Sox2 has also been shown to play an essential role in self-renewal and maintenance of cancer stem-like cell populations in HCC. (42) Therefore, TGF-β signaling may counterbalance Sox2 in cancer initiating and progenitor cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It plays important roles in cell proliferation, apoptosis, aging, inflammation and metabolism (3032). In addition, it can affect tumorigenesis, development and metastasis of a tumor (33,34). Sirt1 is heterogeneously expressed in tumor, which is closely related to tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, the suppressive effects of SOX2 on HBV RNA transcription and HBV protein production are also confirmed in the BALB/c mice sera and liver tissues. We suggested that SOX2 may act as a restriction factor to repress HBV replication, not only during the acute infection, but also in the chronic infection and the development of liver diseases [12,20]. Previous studies have reported that HBV mRNA was lower in the HCC tissues relative to the non-tumor liver tissues [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…SOX2 is also involved in the progression of HCC. For instance, SOX2 is a main downstream regulator of the silent information regulator 1 (SIRT1)-mediated self-renewal and tumorigenicity of liver cancer stem cells [12]. Moreover, overexpression of SOX2 and its co-factor Oct4 can be novel predictors of poor prognosis for patients undergoing resection of HCC [10].…”
Section: Introductionmentioning
confidence: 99%